Application of Artificial Intelligence in Medical Diagnosis: A Systematic Analysis of the Literature on Progress and Challenges - Abdul Ghafur (Penelitian dan Pengembangan Ilmu, 2024)
The application of artificial intelligence (AI) in medical diagnosis has become an increasingly important topic in modern medicine. This systematic literature review aims to evaluate progress, challenges, and opportunities in the application of AI in medical diagnosis. Through analysis of a number of relevant articles, we highlight the role of AI in improving accuracy, speed and efficiency in the diagnosis process. However, we also identified a number of challenges that need to be addressed, including technical, ethical and practical aspects. Nonetheless, the opportunities for further development in the application of AI in medical diagnosis are also enormous. By better understanding these advances, challenges, and opportunities, it is hoped that we can accelerate the adoption of AI in clinical practice and improve overall patient outcomes.